Utility of preoperative natriuretic peptides and echocardiographic parameters in predicting new-onset atrial fibrillation after coronary artery bypass grafting: a prospective comparative study. (22nd September 2015) - Gibson, PH; Croal, BL; Cuthbertson, BH; Rae, D; McNeilly, JD; Gibson, GA; Jeffrey, RR; Buchan, KG; El-Shafei, H; Hillis, GS
Abstract : Background: Atrial fibrillation (AF) is a common complication after coronary artery bypass grafting (CABG). We prospectively compared the ability of echocardiographic parameters and the cardiac neurohormones, B-type natriuretic peptide (BNP) and N-terminal pro-BNP (NT pro-BNP), to predict AF in this setting. Methods: We recruited 275 patients undergoing non-emergency CABG. Patients with previoius atrial arrhythmia or undergoing valve surgery were excluded. Echocardiography was performed and natriuretic peptide levels were measured 24 h before surgery. Holter monitoring was used to detect postoperative AF. The primary end-point was postoperative AF lasting longer than 30 s. Results: The only significant echocardiographic predictors of postoperative AF (n  =  107, 39%) were the transmitral E to A-wave ratio and the early mitral annulus velocity. There were no significant differences in left ventricular ejection fraction (LVEF). Levels of BNP and NT pro-BNP were higher in patients who developed AF. Both natriuretic peptides, but none of the echocardiographic parameters, remained independently predictive in multivariate analysis. The optimum cut-points for predicting AF were 31 pg/ml for BNP (odds ratio (OR) 2.74, p = 0.001) and 74 pg/ml for NT pro-BNP (OR 2.74, p = 0.003). Conclusion: Levels of BNP and NT pro-BNP are independent predictors of AF following isolated CABG. In contrast, none of the echocardiographic parameters assessed, including LVEF and measures of left ventricular filling pressure were independently predictive. The results suggest that other factors are also important in the aetiology of AF after CABG.